Optimizing The Karang Mumus River School (SeSuKaMu) as An Innovation to Revitalize the River - Khaerani, Thalita Rifda; Tiara Febriyanti (Universitas Pendidikan Ganesha, 2024)
The condition of the Karang Mumus River has been decreased from the water quality and physical condition of the river This situation has become the main focus of the government in an effort to restore the function and environment of the river as a source of meeting water needs in East Kalimantan. Community service activities aim to provide examples to the community through activities to restore the area around the river by sowing tree seeds that will be planted along the riverbanks with the Karang Mumus River Trash Pickup Movement Community which initiated the movement to save the river from ecological crisis. The method of approach is observation by discussing and interviewing information from environmental activists about SeSuKaMu, then analyzed descriptively. Community service activities such as the SeSuKaMu reforestation restoration carried out by the Community Service Team of the FISIP UNMUL Bachelor of Public Administration Study Program together with community resulted in outcomes in the form of the formation of environmental awareness and increasing community education on the importance of river conservation through activities to reforest the riverbank area and sowing tree seeds.